Dual-frequency acousto-ultrasonic sensing of impact damage in composites for mitigating signal instability. (March 2022) - Gong, Chen; Wu, Qi; Zhang, Hanqi; Wang, Rong; Xiong, Ke; Okabe, Yoji; Yu, Fengming
Signal instability due to temperature fluctuations, sensor degradation, and debonding introduces additional amplitude loss in the detected signals during acousto-ultrasonic detection, which may be falsely attributed to defects in a structure. First, we determined that the amplitudes of both high-frequency and low-frequency Lamb waves decrease after propagation through a damaged area. Then, we found that the amplitude ratio of such waves not only exhibits a downward trend but is also immune to fluctuations in the input signals. A qualitative numerical expression was proposed to explain this phenomenon, and preliminary experiments were conducted to demonstrate that the amplitude ratio is an effective parameter for mitigating instability in signal detection. Particularly, the number of impacts on a composite laminate was evaluated with respect to changes in the input signal amplitude. Notably, this method can be further simplified by designing a dual-frequency input signal. After conclusively validating the performance of the novel method in a composite subjected to temperature fluctuations, we conclude that the proposed acousto-ultrasonic detection method is robust in mitigating signal instability, and that it yields reliable information for damage evaluation.